Battery level monitoring system - Aiesyah, Ghazali (2012)
The purpose of battery level monitoring system is to measure and monitors the fundamentals parameter of a rechargeable battery. The parameters that will be measured and monitored are the output voltage of the battery. The output voltage is used in the real-time calculation of the remaining time before the rechargeable battery is exhausted and in case of malfunction. The LCD will be used as the voltage output display. For this project a battery charger circuit for 12 V sealed lead acid battery is develop. The monitoring of charging and discharging state of the battery and also the battery voltage value is displayed by using LCD. It is consist of three basic part that is the charging circuit, controller circuit and the monitoring circuit. The battery charger is able to charge a sealed lead acid battery and able to protect the battery from overcharge. Besides that, it also will show the battery voltage value. The brain of the system is a PIC16F876A, the microcontroller. The processes are managed by this microcontroller, that is including the data need to be displayed on the LCD screen. The instructions are given by using push buttons from a menu option. There is also a timing counter to stop the charging from been overcharge the battery to prevent damage to the battery.